Doing Research in Counselling and Psychotherapy - McLeod, John (Los Angeles Sage, 2021)
A highly practical and accessible guide that throws a lifebelt to any counselling trainee or practitioner learning about the research process
Include bibliography reference and index material.
Keywords: Counseling Research Methodology -- Psychotherapy Research Methodology